2020
DOI: 10.1159/000512277
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Calcium Signaling in Regulation of Epithelial-Mesenchymal Transition

Abstract: Despite substantial advances in the field of cancer therapeutics, metastasis is a significant challenge for a favorable clinical outcome. Epithelial to mesenchymal transition (EMT) is a process of acquiring increased motility, invasiveness, and therapeutic resistance by cancer cells for their sustained growth and survival. A plethora of intrinsic mechanisms and extrinsic microenvironmental factors drive the process of cancer metastasis. Calcium (Ca<sup>2+</sup>) signaling plays a critical role in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 309 publications
(242 reference statements)
0
11
0
Order By: Relevance
“…Calcium is the most universal second messenger, mediating signaling pathways that control cell cycle, gene expression, excitability, trafficking, secretion, and cell death [ 2 , 56 , 91 94 ]. Changes is free cytosolic Ca 2+ also facilitate cell motility, differentiation, and tumorigenesis [ 95 97 ]. In intracellular parasites, host cell invasion [ 4 , 48 , 98 ] and egress are also Ca 2+ dependent [ 54 , 99 103 ].…”
Section: Ion Channel Repertoiresmentioning
confidence: 99%
“…Calcium is the most universal second messenger, mediating signaling pathways that control cell cycle, gene expression, excitability, trafficking, secretion, and cell death [ 2 , 56 , 91 94 ]. Changes is free cytosolic Ca 2+ also facilitate cell motility, differentiation, and tumorigenesis [ 95 97 ]. In intracellular parasites, host cell invasion [ 4 , 48 , 98 ] and egress are also Ca 2+ dependent [ 54 , 99 103 ].…”
Section: Ion Channel Repertoiresmentioning
confidence: 99%
“…Ca 2+ , a ubiquitous second messenger, is critical to cancer development, including metastasis and therapy resistance [ 17 ]. Ca 2+ has been widely demonstrated to manipulate events critical to metastasis, including the EMT [ 112 ], invadosome formation, ECM degradation [ 113 ] and angiogenesis [ 114 ]. Serum Ca 2+ level is positively associated with the risk of node metastasis in endometrial and breast cancer [ 115 , 116 ], but low serum calcium level indicates poor distant metastasis-free survival of patients with nasopharyngeal carcinoma [ 117 ].…”
Section: Roles Of Calcium Signaling In Cancer Metastasismentioning
confidence: 99%
“…It has also been shown that calcium regulates mitochondrial and cellular reactive oxygen species (ROS) levels, the latter mainly through the regulation of NADPH oxidases [ 13 ]. Besides its role in cell proliferation, calcium homeostasis is involved in epithelial-mesenchymal transition (EMT) [ 14 ]. EMT is involved in the formation of metastasis through losing the epithelial phenotype and increasing the expression of proteins that promote unstable junctions between epithelial cells such as N-cadherin [ 15 ], thereby being another important factor determining cancer progression.…”
Section: Introductionmentioning
confidence: 99%